2003
DOI: 10.1111/1467-9787.00306
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk and Uncertainty: Insights from Yucca Mountain

Abstract: This study examines the effects of the risk from transporting high-level radioactive waste to the proposed Yucca Mountain repository on housing location decisions in Southern Nevada. Using data from a survey of southern Nevada households, we develop a model-based subjective risk estimate for each household. We then explore different factors that may influence the household's location decisions if the proposed transportation route is ultimately chosen for nuclear waste transport. We extend the conventional expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…For Japan, Yamane et al (2011) found that land prices fell in the neighborhood of a spent fuel reprocessing plant at the time of the pilot carry-in of spent fuels. Riddel et al (2003) found in a stated choice experiment that perceived risk decreased with distance to a planned nuclear waste transportation route and that higher perceived risk resulted in a higher probability of moving away from the route.…”
Section: Valuation Studiesmentioning
confidence: 99%
“…For Japan, Yamane et al (2011) found that land prices fell in the neighborhood of a spent fuel reprocessing plant at the time of the pilot carry-in of spent fuels. Riddel et al (2003) found in a stated choice experiment that perceived risk decreased with distance to a planned nuclear waste transportation route and that higher perceived risk resulted in a higher probability of moving away from the route.…”
Section: Valuation Studiesmentioning
confidence: 99%
“…They obtain a positive distance gradient of USD 330-495 per mile. A study related to the present paper is by Riddel, Dwyer, and Shaw (2003), who estimate the effect of several planned nuclear waste transportation routes from power plants to the Yucca Mountain (Nevada) repository. They find evidence that perceived risk decreases with distance to the planned transportation route and that higher perceived risk results in a higher probability of moving away from the route.…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of this work is to study in detail the location selection in NPP construction. In this process of site selection for building an NPP in Vietnam, the main factors are discussed based on the regulations for environmental radiation protection of a nuclear power plant [30] and some previous works [31][32][33][34][35]: Reliability and Security of the Site (C1), Site Characteristics Corresponding to Environmental Compatibility (C2), Economic Rationality (C3), and Technical Feasibility (C4). The hierarchical structures of the FANP model are shown in Figure 4.…”
Section: Case Studymentioning
confidence: 99%